The Offences of Stealing, Robbery and Armed Robbery Distinguished - Alili, Ngozi (NIU Journal of Humanities, 2017)
This work examined the property related offences of stealing (theft), robbery and armed robbery and draws a dividing line between them as legal concepts. It is observed that persons accused of committing any or all of these offences have  common state of mind, which is to fraudulently or dishonestly deprive the owners or persons in possession of the subject matters of these offences permanently of their rights or interest in them under different circumstances or modes of operation. In the case of stealing or theft, no harm or threat is posed to the life and limb of the victim as the accused simply takes his victimâ€™s property without his knowledge, consent or authorization. But in the case of robbery and armed robbery, there is threat and even application of force and sometimes the possession and use of dangerous weapons by the accused in actualizing his intention. It is not therefore surprising that legal consequences, sanction or punishment accruing to the accused in each case is a measure of the physical element of the offence, otherwise called the actus reus.